PENGARUH LOKASI TUMBUH TERHADAP SENYAWA FITOKIMIA PADA BUAH, BIJI, DAUN, KULIT BUAH TANAMAN TAKOKAK (Solanum torvum) - Nunuk Helilusiatiningsih; Titik Irawati (BUANA SAINS, 2021)
Takokak was a plant that was widespread in Indonesia and quite a lot is made culinary at this time. Research on takokak eggplant was developed due to the high content of phytochemical compounds. The problem that exists was that this plant had not been planted by many people but grows by itself in various locations. The purpose of this study was to know the content of phytochemical compounds in the fruit, seeds, and leaves of takokak that grow and develop in different locations. The experimental design used quantitative tests including antioxidant activity, total phenol, tannin content, flavonoids. The locations studied are at Mojokerto and Malang city. The research resulted show that there were differences in phytochemical content, the best data was eggplant takokak originating in the city of Batu, East Java. The Takokak eggplant plant thrives and had higher levels of bioactive/phytochemical compounds in the sub-tropical climate highlands near the mountains of Batu, Malang.